Pre-event meals: High or low glycemic index foods? - Burke, L. (1998)
Our study showed that the intake of large amounts of carbohydrate during prolonged moderate-intensity exercise, according to current sports nutrition guidelines, maintained the fuel needs of our athletes in our endurance test. Athletes don't need to worry about the glycemic index of the foods they eat before competing.